Odpowiedzi

Najlepsza Odpowiedź!
2010-03-21T18:53:08+01:00
-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30
x=-5


-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15
x=1,5


4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10
x=-5


-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-4+2x-2x-4=3x-1+2x-5-7+3x
2x-2x-3x-2x-3x=-1-5-7+4+4
-8x=-5
x=⅝


(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
4x-5+x-7-2x+8=-3x+4-x+6
4x+x-2x+3x+x=4+6+5+7-8
7x=14
x=2
2010-03-21T19:03:44+01:00
-6(x+1)=2
-6x-6=2
-6x=8
x=-8\6
x=-1 1\3

-7(x-2)=3x-1
-7x+14=3x-1
-10x=-15
x=15\10
x=1,5

4(x-1)=6(1+x)
4x-4=6x+6
-2x=10
x=-5

-4(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-16+8x-2x-4=3x-1+2x-5-7+3x
6x-20=8x-13
-2x=7
x=-7\2
x=-3,5

(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
4x-5+x-7-2x+8=-3x+4-x+6
3x-4=-4x+10
7x=14
x=2